Analisis Keselarasan Pemanfaatan Ruang Kecamatan Sewon Bantul Tahun 2006, 2010, 2014 Terhadap Rencana Detail Tata Ruang Kawasan (RDTRK 2008-2018) - Ansory, Harmi Hakim; , DR.Ir. Imam Hardjono, M.Si (2016)
Rapid population growth and accompanied by ever increasing economic needs led to the need for space has increased as well, resulting in a change in the use of space for purposes of human activities in the region. Lots going expansion of the space utilization of non rice field, so the construction is based on a plan is very important to do in order to avoid the problems that will occur in the future. This study aims to determine the results of the use of remote sensing technology and geographic information systems for the analysis of alignment and to know result alignment development with land-use planning. The materials used in this study is the Quickbird satellite imagery District of Sewon result of the recording process in 2006, 2010, 2014 and then map a plan block space utilization (RDTRK Years 2008-2018). The method used is by using Quickbird satellite image interpretation techniques to obtain data space utilization in 2006, 2010, 2014, and then backed up by a field survey on December 27, 2016. Analysis of the results is done by using a geographic information system, using software AcrGis 10.1. The analysis technique used is the technique of overlaying (overlay) between Map Use of Space 2006, 2010, and 2014 with Plan Map Block Space Utilization which has been prepared by the Government of Bantul, in order to obtain Map Alignment Space Utilization with RDTRK District of Sewon, 2006, 2010 , and 2014. This research resulted in six pieces of the map, ie Map Land Use District of Sewon, 2006, 2010, and 2014. The Land Use Map Alignment District of Sewon, 2006, 2010, and 2014.